Correction: Ferraresi et al. Resveratrol Contrasts LPA-Induced Ovarian Cancer Cell Migration and Platinum Resistance by Rescuing Hedgehog-Mediated Autophagy. Cells 2021, 10, 3213 - Alessandra Ferraresi; Andrea Esposito; Carlo Girone; Letizia Vallino; Amreen Salwa; Ian Ghezzi; Suyanee Thongchot; Chiara Vidoni; Danny N. Dhanasekaran; Ciro Isidoro (Cells, 2025)
In the original publication [...]